SENP1-Sirt3 axis regulates type II alveolar epithelial cell activity to confer resistance against oxidative damage in lung tissue - Mingming Zhang; Xin Lin; Jianli He; Yong Zuo; Qiuju Fan; Innocent Agida; Hongsheng Tan; Caiying Zhu; Jinke Cheng; Tianshi Wang (Redox Biology, 2025)
Oxidative damage exacerbates pulmonary fibrosis by impairing alveolar type II epithelial (AT2) cell function. This study demonstrates that the SUMO-specific protease 1 (SENP1)-Sirtuin 3 (Sirt3) axis, critical for mitochondrial redox regulation, is suppressed in AT2 cells during lung injury. In bleomycin-induced pulmonary fibrosis models, activating the SENP1-Sirt3 axis via Sirt3 SUMOylation site mutation (Sirt3 K223R) reduced Superoxide Dismutase 2 (SOD2) acetylation, thereby lowering mitochondrial reactive oxygen species (mtROS) accumulation and apoptosis. This intervention increased AT2 cell proliferation and differentiation into alveolar type I cells while reducing Keratin 8 (KRT8)+ transitional cell number, a profibrotic population. Additionally, SENP1-Sirt3 activation attenuated inflammation and fibrosis in lung tissue. Transcriptomic analysis linked the axis to enhanced Wnt signaling and lipid metabolism pathways, promoting AT2 stemness. Antioxidant N-acetylcysteine (NAC) supplementation mirrored these benefits, reinforcing ROS clearance as a therapeutic mechanism. These findings highlight SENP1-Sirt3 as a pivotal regulator of AT2 resilience, offering a potential strategy to mitigate fibrosis by targeting mitochondrial oxidative stress and cellular plasticity.